Rethinking the global food crisis: The role of trade shocks - Headey, Derek D. (International Food Policy Research Institute, 2010)
From 2003 to their peak in mid 2008, the nominal prices of maize and wheat roughly doubled, while those of rice tripled in a matter of months rather than years. Although fundamental factors were clearly responsible for shifting the world to a higher equilibrium price during this time, there is little doubt that when food prices peaked in June 2008, they soared well above the new equilibrium price. Numerous arguments have been proposed to explain overshooting, including financial speculation, depreciation of the United States (U.S.) dollar, low interest rates, and reductions in grain stocks. However, observations that international rice prices surged in response to export restrictions by India and Vietnam suggested that trade-related factors could be an important basis for overshooting, especially given the very tangible link between export volumes and export prices. In this paper, we revisit the trade story by closely examining monthly data from the largest export markets for rice (Thailand), wheat, maize and soybeans (the United States). In each case, we find that large surges in export volumes preceded the price surges. The presence of these demand surges, together with back-of-the-envelope estimates of their price impacts, suggest that trade events played a much larger and more pervasive role than previously thought. This further implies that improving the international grain markets should be a central focus of the international policy agenda going forward.